IMPACT OF BIOFLAVONOIDS ON HYPERHOMOCYSTEINEMIA-INDUCED CHANGES IN METABOLISM OF HYDROGEN SULFIDE IN THE MYOCARDIUM AND AORTA OF MALE AND FEMALE RATS - Мельник, А.В.; Волощук, Н.І. (World of Medicine and Biology, 2016)
Bioflavonoids genistein and quercetin exhibit pronounced cardio and vasoprotective action that is associated with their antioxidant and anti-inflammatory properties. Their effect on the metabolism of hydrogen sulfide (H2S) in the cardiovascular system of rats of different sex in the conditions of hyperhomocysteinemia remains unexplored. Therefore, we studied the influence of genistein and quercetin on hyperhomocysteinemia-induced changes of H2S content, activity of the synthesis and utilization of H2S in the myocardium and aorta of male and female rats. It was found that the use of genistein under hyperhomocysteinemia condition counteracts the deficiency of H2S in the cardiovascular system in rats of both sexes. In addition, genistein prevents the decrease in activity of H2S-synthesizing enzymes and inhibits strengthening the processes of utilization of H2S in male and female rats. Under these conditions, the impact of quercetin on the performance of the indexes of H2S system in the myocardium and aorta of male and female rats was significantly lower than genistein.